1989
DOI: 10.1200/jco.1989.7.11.1733
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacology of a novel diarylsulfonylurea anticancer agent.

Abstract: LY186641 (diarylsulfonylurea, [DSU]) is a novel anticancer agent because of its unique diarylsulfonylurea chemical structure, broad-spectrum antisolid-tumor activity in preclinical models, presumed novel mechanism of action and preclinical toxicities of methemoglobinemia (Met Hgb) and decreased red blood cell (RBC) survival. In this study, the in vitro drug sensitivity of human tumors as well as clinical pharmacology and toxicology of DSU in patients with cancer were examined. DSU was administered orally, dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…Phase I trials established an acceptable toxicity profile and a maximum tolerated dose for the drug [1,2] The three cases reported here represent the only three patients in whom Solufenur and warfarin were coadministered. In all three, a marked prolongation of PT occurred while the two drugs were given, which promptly corrected when the Sulofenur was discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…Phase I trials established an acceptable toxicity profile and a maximum tolerated dose for the drug [1,2] The three cases reported here represent the only three patients in whom Solufenur and warfarin were coadministered. In all three, a marked prolongation of PT occurred while the two drugs were given, which promptly corrected when the Sulofenur was discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…First-generation DSUs, which are structurally similar to glibenclamide with an unknown anticancer mechanism, reached clinical application in some cases but with poor tolerability and disappointing results [50,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Since the end of the 1980s, the anticancer effects of DSUs-compounds structurally similar to oral antidiabetic glibenclamidehave been described in vitro and in vivo [50]. In particular, several authors reported antitumor activity of N-(4-methylphenylsulfonyl)-NЈ-(4-chlorophenyl)urea (LY181984) and N-(5-indanylsulfonyl)-NЈ-(4-chlorophenyl)urea (LY186641; sulofenur) in in vitro and in vivo models of solid tumors, with modest activity in hematologic cancer [50 -53].…”
Section: From Glibenclamide To Dsusmentioning
confidence: 99%
See 2 more Smart Citations